Face of the deep : a theology of becoming - Keller, Catherine, 1953- (Routledge, 2003)
"Face of the Deep is the full theology of creation from the primal chaos. It proposes a creation ex profundis - creation out of the watery depths - both as an alternative to the orthodox power-discourse of creation from nothingness, and as a figure of the bottomless process of becoming." "From within a dangerous and crowded postmodernity, Catherine Keller's impassioned, graceful meditation opens up an ultimately hopeful space within the magnetic depths of cosmic origin. As a landmark work of immense significance for Jewish and Christian theology, gender studies, literature, philosophy and ecology, Face of the Deep stretches our originary story to profound new horizons, rewriting the starting point for western spiritual discourse."